2022
DOI: 10.21203/rs.3.rs-1242718/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Harvesting of Proteins with Electroporation In Vivo Facilitates the Profiling of Spatial Differential Protein Expression in Tumors

Abstract: Background. Excision tissue biopsy, while central to cancer treatment and precision medicine, presents risks to the patient and does not provide a sufficiently broad and faithful representation of the heterogeneity of sampled solid tumors. Methods. Here we introduce e-biopsy – a novel concept for molecular profiling of solid tumors using molecular extraction with electroporation. As e-biopsy provides access to the molecular composition of a solid tumor, it potentially facilitates tumor diagnostics without tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Recently, we introduced a novel, minimally invasive tissue sampling approach with molecular biopsy using electroporation, termed 'e-biopsy', that selectively extracts liquids with informative proteomes in animal models in liver cancer 14 and brain melanoma 15 in vitro and in breast cancer in vivo, enabling in vivo spatial mapping of differential protein expression. 16 Electroporation-based technologies have been successfully used to permeabilize the cell membrane in vivo, enabling a broad set of applications ranging from tumour ablation to targeted delivery of molecules to cell populations and tissues. 17 However, to the best of our knowledge, such a technology is not yet available and has not been reported in the literature for minimally invasive human tissue molecular sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we introduced a novel, minimally invasive tissue sampling approach with molecular biopsy using electroporation, termed 'e-biopsy', that selectively extracts liquids with informative proteomes in animal models in liver cancer 14 and brain melanoma 15 in vitro and in breast cancer in vivo, enabling in vivo spatial mapping of differential protein expression. 16 Electroporation-based technologies have been successfully used to permeabilize the cell membrane in vivo, enabling a broad set of applications ranging from tumour ablation to targeted delivery of molecules to cell populations and tissues. 17 However, to the best of our knowledge, such a technology is not yet available and has not been reported in the literature for minimally invasive human tissue molecular sampling.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed protocols for targeted delivery of electric fields to tissues to induce focused electroporation at predetermined regions in organs 23 . More recently, we have shown that electroporation-based molecular sampling, termed "e-biopsy", selectively extracts liquids from solid tissues with informative proteomes in animal models in liver cancer 24 and brain melanoma 25 in vitro and from breast cancer in vivo, enabling in vivo spatial mapping of differential protein expression 26 . To the best of our knowledge, such a technology…”
Section: Introductionmentioning
confidence: 99%